The effects of propolis on sperm quality, reproductive organs and testicular antioxidant status of male rats treated with cyclosporine-A - Baykalir, B. Gul; Seven, P. Tatli; Gur, S.; Seven, I. (Brazilian Coll Animal Reproduction, 2016)
This study was designed to determine the effects of propolis on the quality of sperm and reproductive organs in male rats treated with cyclosporine-A. In this study, 24 male Sprague-Dawley rats (280-300 g BW) at 8-10 weeks of age were used. The rats were randomly divided into control and 3 treatment groups. Each rat was placed into a cage. During 21 days (experimental period), Group 1 served as control group; Group 2 (CsA) was given 15 mg/kg BW/day of CsA by subcutaneously; Group 3 (P) was given 100 mg/kg BW/day of propolis by gavage; Group 4 (CsA+P) was given 15 mg/kg BW/day of CsA subcutaneously and 100 mg/kg BW/day of propolis by gavage. Administration of CsA to rats decreased sperm motility (P < 0.01) and sperm concentration (P < 0.01), and it increased total abnormal sperm rates (P < 0.05) as compared with the control group. Significant improvements were observed in the sperm motility (P < 0.01) and total abnormal sperm rates (P < 0.05) in CsA+P group. No significant differences were observed in the weights of right and left testes among all groups. The weight values of right and left epididymis were found similar to each other in CsA administrated groups. Seminal vesicle (P < 0.01) and prostat glands weights (P < 0.01) were significantly higher in CsA+P group than CsA group. As a result, it was determined that oral supplementation of 100 mg/kg of propolis had amendatory effect on the quality of sperm and reproductive organs treated with CsA administered rats. CsA treatment caused a significant increase in MDA level (P < 0.01) and significant decreases (P < 0.01) in GSH level and CAT activity when compared with the control group. Ingestion of propolis by CsA-treated rats significantly decreased the MDA level and significantly increased the GSH level when compared with the CsA alone group (P < 0.01).
Keywords: cyclosporine-A; propolis; rat; reproductive organs; sperm characteristics